Dynamics of MDR Enterobacter cloacae outbreaks in a neonatal unit in Nepal: insights using wider sampling frames and next-generation sequencing. (3rd January 2015) - Stoesser, N.; Sheppard, A. E.; Shakya, M.; Sthapit, B.; Thorson, S.; Giess, A.; Kelly, D.; Pollard, A. J.; Peto, T. E. A.; Walker, A. S.; Crook, D. W.
Abstract: Objectives: There are limited data on Enterobacter cloacae outbreaks and fewer describing these in association with NDM-1. With whole-genome sequencing, we tested the hypothesis that a cluster of 16 E. cloacae bacteraemia cases in a Nepali neonatal unit represented a single clonal outbreak, using a wider set of epidemiologically unrelated clinical E. cloacae isolates for comparison. Methods: Forty-three isolates were analysed, including 23 E. cloacae and 3 Citrobacter sp. isolates obtained from blood cultures from 16 neonates over a 3 month period. These were compared with two contemporaneous community-associated drug-resistant isolates from adults, a unit soap dispenser isolate and a set of historical invasive isolates ( n  = 14) from the same geographical locality. Results: There were two clear neonatal outbreaks and one isolated case in the unit. One outbreak was associated with an NDM-1 plasmid also identified in a historical community-associated strain. The smaller, second outbreak was likely associated with a contaminated soap dispenser. The two community-acquired adult cases and three sets of historical hospital-associated neonatal isolates represented four additional genetic clusters. Conclusions: E. cloacae infections in this context represent several different transmission networks, operating at the community/hospital and host strain/plasmid levels. Wide sampling frames and high-resolution typing methods are needed to describe the complex molecular epidemiology of E. cloacae outbreaks, which is not appropriately reflected by routine susceptibility phenotypes. Soap dispensers may represent a reservoir for E. cloacae and bacterial strains and plasmids may persist in hospitals and in the community for long periods, sporadically being involved in outbreaks of disease.